2015
DOI: 10.30649/denta.v9i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Daya Hambat Minyak Hati Ikan Hiu Terhadap Pertumbuhan Bakteri Porphyromonas gingivalis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…They were both tested on both gramnegative bacteria, for example; Escherichia coli and Pseudomonas aeruginosa, in addition to gram-positive bacteria such as Staphylococcus aureus and Streptococcus pneumoniae. Similarly, another investigation undertaken by Agustina (2015) 14 showed that shark liver oil has inhibitory properties in relation to Porphyromonas gingivalis bacteria. Alkylglycerol can bind to phospholipid cell membrane changing its structure to membrane fluidity and antioxidants and protecting the structure and function of membranes in white blood cells and macrophages.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…They were both tested on both gramnegative bacteria, for example; Escherichia coli and Pseudomonas aeruginosa, in addition to gram-positive bacteria such as Staphylococcus aureus and Streptococcus pneumoniae. Similarly, another investigation undertaken by Agustina (2015) 14 showed that shark liver oil has inhibitory properties in relation to Porphyromonas gingivalis bacteria. Alkylglycerol can bind to phospholipid cell membrane changing its structure to membrane fluidity and antioxidants and protecting the structure and function of membranes in white blood cells and macrophages.…”
Section: Discussionmentioning
confidence: 85%
“…12 Centrophorus moluccensis is a type of shark whose liver oil is commonly extracted for subsequent use for medicinal purposes. 13 Previous research conducted by Agustina (2015) 14 indicated that shark liver oil has inhibitory properties in relation to Porphyromonas gingivalis bacteria. The alkylglycerol contained in sharks can even protect the structure and function of white blood cell membranes and macrophages.…”
Section: Introductionmentioning
confidence: 98%
“…Oleh karena itu, diperlukan terapi alternatif untuk mengobati penyakit periodontal tanpa efek samping. [6] Kemampuan daya hambat bakteri pada biji kelor sudah banyak dilaporkan, salah satunya dari penelitian Christian dkk (2015) menyimpulkan bahwa terdapat efek antibateri ekstrak daun dan biji kelor terhadap bakteri Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. [7] Bakteri lain yang ada di dalam rongga mulut adalah Porphyromonas gingivalis.…”
Section: Pendahuluanunclassified
“…[10], [11] Menurut Sendy dkk (2014) menyatakan bahwa terdapat daya antibakteri ekstrak daun sirih merah (Pipper crocatum) terhadap Porphyromonas gingivalis. Kartasapoetra (1992), menyatakan dari hasil kromatogram, diketahui daun sirih merah mengandung minyak atsiri yang sepertiga bagiannya terdiri atas fenol-fenol yang khas yang disebut betelfenol atau aseptosol, alkaloid, flavonoid dan polevenolad sedangkan kavikol yang khasiatnya bakterisidal yang merupakan eugenol methylester diperkirakan khasiatnya sama dengan eugenol sebagai bahan antiseptik, [15], [16] Moringa stenopetala adalah tanaman asli dari Kenya dan Ethiopia. Moringa stenopetala menghasilkan dedaunan yang dapat dimakan, buah, dan biji yang kaya akan asam amino esensial, vitamin, dan mineral.…”
Section: Mean ± Sd P-valueunclassified